Core Java™ 2 Volume I - Fundamentals, Seventh Edition - Horstmann, Cay; Cornell, Gary (Sun Microsystems Press Java series., 2004)
Completely revised and up-to-date coverage of Generic programming, restrictions and limitations, type bounds, wilcard types, and generic reflection Swing GUI development, including input validation and other enhancements Exception handling and debugging, including chained exceptions, stack frames, assertions, and logging Streams and files, the new I/O API, memory-mapped files, file locking, and character set encoders/decoders Regular expressions using the powerful java.util.regex package Inner classes, reflection, and dynamic proxies Application packaging and the Preferences API The seventh edition of Core Java™ 2, Volume I, covers the fundamentals of the Java 2 Platform, Standard Edition (J2SE™). A no-nonsense tutorial and reliable reference, this book features thoroughly tested real-world examples. The most important language and library features are demonstrated with deliberately simple sample programs, but they aren't fake and they don't cut corners. More importantly, all of the programs have been updated for J2SE 5.0 and should make good starting points for your own code. You won't find any toy examples here. This is a book for programmers who want to write real code to solve real problems. Volume I concentrates on the fundamental concepts of the Java language, along with the basics of user-interface programming and provides detailed coverage of Object-oriented programming Reflection and proxies Interfaces and inner classes The event listener model Graphical user-interface design with the Swing UI toolkit Exception handling Stream input/output and object serialization Generic programming For the same real-world treatment of enterprise features and advanced user-interface programming, look for the forthcoming new edition of Core Java™ 2, Volume II-Advanced Features. It includes new sections on metadata and other J2SE 5.0 enhancements along with complete coverage of: Multithreading • Distributed objects • Databases • Advanced GUI components • Native methods • XML Processing • Network programming • Collection classes • Advanced graphics • Internationalization • JavaBeans.